Dengue-related term identification - Teo, Han Jun (2015)
Dengue is caused by the dengue virus, in short DENV. It is a mosquito-borne flaviviru that belongs to a single stranded RNA positive-strand virus of the family Flaviviridae, genus Flavivirus. Dengue is found mostly in urban and semi-urban areas globally. It is transmitted to humans by the Aedes aegypti or more rarely the Aedes albopictus mosquito, which feed during the day. As a result, this causes Dengue fever, a fatal disease among children and elderly in some Asian countries. And unfortunately, there is no cure for dengue fever. In this project, a corpus of literature that describes dengue related research is extracted from the PubMed /Medline. The next step is to identify the biomedical terms that frequently and exclusively appear in the corpus are retrieved. Subsequently after all the terms are identified, we will try to combine all the results and determine if they are co-related in the dengue development. The final results have shown that platelet count is a key term towards detecting and curing dengue fever. The cures in the dengue virus has also been derived in our research.